Population structure and selective signature of sheep around Tarim Basin - Zhang, Jihu; Zhang, Cheng-long; Tuersuntuohe, Mirenisa; Liu, Shudong (Frontiers in Ecology and Evolution, 2023)
Extreme climate change may lead to a decline in biodiversity and species extinction. And it also results in different population structure and genetic diversity of sheep. Therefore, studying the effects of extreme climate change on the distribution pattern of sheep is of great value. We used Illumina Ovine SNP 50K BeadChip to study the sheep around in southern Xinjiang of China, living around the Taklimakan Desert. Among them, 6 sheep breeds were from Xinjiang, China, and 3 sheep breeds were from other countries (Indian, Iran and Bangladeshi). We examined their genetic diversity and population structure and Genes related to year-round estrous in sheep were obtained by selective sweep. The principal component analysis, Admixture and Neighbor-Joining tree showed that a distinct pattern of population structure was observed in 9 sheep breeds. The candidate genes related to year-round estrous were ZO2, IGF1, TSHB and DLG1, and the candidate genes related to sheep reproductive performance were BMP4, LRP8, NF1, and INSL3. This study contributes to a better understanding of the genetic structure and population history of sheep populations in the Taklimakan Desert environment, as well as the regulatory mechanisms of year-round estrous in sheep in the desert environment, which has important implications for the global livestock industry to cope with the challenges of rapidly changing climate and to explore important economic traits.